Evaluation Of Middle Cerebral/Umbilical Artery Resistance And Pulsatility Indices Ratio As Predictors Ffor Fetal Well-Being And Neonatal Outcome In Preeclampsia With Or Without Intrauterine Growth Restriction (Journal of Pharmaceutical Negative Results, 2023)
Background Pre-eclampsia is linked to abnormal uteroplacental circulation, which could have a negative perinatal result by affecting foetal growth and oxygenation. Doppler ultrasound is a good tool for examining the aberrant vascular resistance to blood flow in the uteroplacental and fetoplacental circulation. Objective Detection of the middle cerebral to umbilical arteries with accuracy Prediction of foetal health and newborn outcome using the Doppler indices ratio in pregnancies complicated by pre-eclampsia with or without signs of intrauterine growth restriction. Methods This study included 90 pregnant patients attending to Kasr El-Ainy Hospital high risk pregnancy unit from 2014 to 2016. Patients were divided into two groups, first group included 30 cases with normal uncomplicated pregnancies. The second group included 60 cases with pregnancies complicated by pre-eclampsia Patients of the preeclamptic group were subdivided further into two subgroups first is mild pre-eclampsia and second is sever pre-eclampsia and all subgroups were assessed for the presence of IUGR. Results IUGR and adverse neonatal outcome were significantly associated with the severity of preeclampsia. The ability of CPR and R.I ratio to predict IUGR in mild group was evaluated; the sensitivity, specificity, positive predictive value, negative predictive value and accuracy for the CPR were 100%, 96%, 83.3%, 96% and 96.7% respectively. The corresponding figures for the RI ratio were 80%, 92%, 66.7%, 95.8% and 90%, respectively. Furthermore, in the sever group, the ability of CPR and R.I ratio to predict IUGR was evaluated ;the sensitivity, specificity, positive predictive value, negative predictive value and accuracy for the CPR were 94.4%, 100%, 94.4%, 92.3% and 96.7%. For detection of adverse neonatal outcome in the mild group, both CPR and R.I ratio showed similar values of sensitivity, specificity, positive predictive value, negative predictive value and accuracy of CPR and R.I ratio in detection of adverse neonatal outcome were 100%, 85.7% , 33.3%, 85, 7% and 86.7% respectively. Where as in the sever group the sensitivity, specificity, positive predictive value, negative predictive value and accuracy of CPR and R.I ratio in detection of adverse outcome were 91.7%, 66.7%, 64.7%, 92.3%, 76.7% and 91.7%, 61.1%, 61.1%, 91.7% and 73.3% respectively. Conclusion When it comes to IUGR and poor neonatal outcomes in the foetuses of preeclamptic and gestational hypertensive women, CPR is a very good predictor. When it comes to detecting IUGR and a poor newborn outcome in pre-eclampsia, CPR is more accurate than R.I ratio.